Yield performance and quality of wine grapes (Vitis vinifera) grafted onto different rootstocks under subtropical conditions - Tecchio, Marco Antonio [UNESP]; Silva, Marlon Jocimar Rodrigues da [UNESP]; Sanchez, Camilo Andre Pereira Contreras [UNESP]; Callili, Daniel [UNESP]; Vedoato, Bruna Thais Ferracioli [UNESP]; Hernandes, Jose Luiz; Moura, Mara Fernandes (Inst Agronomico, 2022)
This study aimed to evaluate the productive performance and physicochemical traits of wine grape cultivars (Cabernet Sauvignon, Syrah, Cabernet Franc, Merlot, and Sauvignon Blanc) grafted on two different rootstocks (IAC 766 Campinas, and 106-8 Mgt) under subtropical conditions. The productive components (number of bunches, production per vine, yield, number of berries per bunch, fresh mass, length, and width of berries) and the grape must physicochemical composition (pH, titratable acidity, soluble solids, and maturation index) were determined after four consecutive harvest seasons. Results from analysis of variance and principal component analysis showed that Cabernet Franc and Syrah were generally more productive than the other ones. In addition to that, Cabernet Sauvignon presented the lowest production and the smallest grape berries of all. With regards to rootstocks, IAC 766 induced higher scions yield than 106-8 Mgt; besides that, IAC 766 had greater affinity with Cabernet Franc and Merlot, which was observed by the increase in the number of bunches per vine, larger and heavier bunches, as well as higher soluble solids content and pH value than the ones in 106-8 Mgt. Furthermore, IAC 766 also induced higher soluble solids content and pH value for Cabernet Sauvignon. Results showed similar effects for Syrah and Sauvignon Blanc, regardless of the rootstocks.
Keywords: vitiviniculture; grafting; physicochemical characteristics; red grapes; white grapes